COMPARISON OF PERSONAL DOSE EQUIVALENT Hp(10) IN 137CS RADIATION BETWEEN THE PRIMARY STANDARDS LABORATORIES OF JAPAN AND AUSTRALIA USING BeO OSL PERSONAL DOSEMETERS. Issue 2 (15th July 2017) - Butler, D J; Kurasawa, T; Litwin, M; Mazaraki, J; Saito, N
Abstract: A comparison of personal dose equivalent Hp(10) for 137 Cs radiation was conducted between the primary standards laboratories of Japan and Australia. A set of 120 commercially available passive BeO OSL dosemeters were used (Dosimetrics GmbH, Munich). The aim was to investigate the precision which could be obtained with this technique, and to confirm the personal dose equivalent delivery methods in each standards laboratory. A dose of 5 mSv was delivered to 40 dosemeters in each country, and 40 dosemeters were used as controls. The result of the comparison was a ratio of Hp(10) in Japan to Australia of 1.006 with a combined standard uncertainty of 3.2%. The statistical uncertainty was 0.32% indicating that passive dosemeters can be used for comparisons of high precision.